Guidelines for the use of human immunoglobulin therapy in patients with primary immunodeficiencies in Latin America (2014)
ABSTRACT: Antibodies are an essential component of the adaptative immune response and hold long-term memory of the immunological experiences throughout life. Antibody defects represent approximately half of the well-known primary immunodeficiencies requiring immunoglobulin replacement therapy. In this article, the authors review the current indications and therapeutic protocols in the Latin American environment. Immunoglobulin replacement therapy has been a safe procedure that induces dramatic positive changes in the clinical outcome of patients who carry antibody defects.